Platební rozkaz v českém a evropském právu - komparativní studie - Nett, Alexander, 1956- (2006)
The goal of this thesis is to describe a czech order for payment procedure and a European order for payment procedure and also refer to differences between them. An order for payment is a kind of ruling. It is issued without hearing, only on the basis of facts claimed by a plaintiff. It is a simplified procedure.